Understanding the impact of chatbots on purchase intention - Soares, Ana Maria (2022)
This paper aims to understand the use of chatbots as digital assistants in e-commerce sites. We investigate the impact of several chatbot attributes, specifically perceived usefulness, perceived ease of use, and trust on consumer attitude and satisfaction with the chatbot, and the effect of these two outcomes on purchase intention. A survey was carried out with 298 valid respondents to test the proposed model. The results indicate significant positive effects of both perceived usefulness and trust on both attitude towards chatbots and satisfaction. The findings did not reveal any significant impact of perceived ease of use on attitude and satisfaction, furthermore, these two outcomes did not significantly influence purchase intention calling for further research to help explain behavioral outcomes towards these relatively new conversational agents.